The becoming of coal mining and the security around it: The case of Colombia - Line Jespersgaard Jakobsen (Danish Institute for International Studies (DIIS), 2020)
Social protection is emerging in Nepal as a key state instrument to reduce social exclusion and inequality by providing cash and social transfers to the most vulnerable households, targeting the socially excluded and challenging inter-generational poverty. In 2016-17, over 2.2 million persons in Nepal benefitted directly from government social protection, for which NRs 32 billion were allocated. When these activities are linked to broader state-building processes, social protection can shape the social contract between citizen and state. It can reduce inequalities rooted in relations based on caste and ethnicity, countering elite monopolisation of political, social and economic capital. However, if handled merely as a technocratic approach to the effects of exclusion and marginalisation, then social protection can risk supporting an existing political settlement that maintains the positions of political, economic and cultural elites. In that Nepal retains caste and ethnic forms of social exclusion and that these have a central role in reproducing entrenched inequalities, is social protection merely a new means for supporting an old political settlement?
Keywords: 330; Kohlenbergbau; Unternehmenssicherheit; Kolumbien